Pola Komunikasi Orang Tua Dalam Meningkatkan Nilai Keberagamaan Generasi Muda Hindu Di Dusun Karang Anyar Lombok Barat - Ni Ketut Feriani; I Nyoman Wijana; I Nyoman Budhita (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2020)
The majority of the people in Karang Anyar Hamlet (almost 90%) are farmers. Due to full concentration in agricultural activities to fulfill the needs of the family's life, eventually taking up too much time, compared to the remaining time available to care for children. The education level of parents is relatively low, only graduating from elementary school, junior high school and some of high school education, but the young Hindu generation has high motivation in carrying out the teachings of Hinduism and Balinese culture inherited from their families, so it is necessary to examine the pattern of care for Hindu families toward their sons and daughters especially in enhancing religious values ​​in order to be able to create harmony in life between Hindus and other religious communities around it. Moreover, the interaction of young Hindu generation with other young people is still condusive. This research is entitled "Parenting Parents in Increasing Religious Values ​​of Young Hindu Generation in Karang Anyar Hamlet, West Lombok" by raising three problems, namely 1) What are the model parenting approaches?, What strategies are used? 3) What are the obstacles of parents in increasing the religious value to the young Hindu generation. The general objective of this research is to photograph and reveal the parenting style of parents in enhancing the religious value of Hindu young generation in Karang Anyar Hamlet, West Lombok. This study uses qualitative methods with qualitative descriptive data analysis. This location was chosen because majority of the parents are busy in agricultural work and the level of education is relatively low but the young Hindu generation has high motivation in carrying out the Hindu teachings. This research combines three theories, namely needs theory, structural functional theory and humanistic theory. Based on the results of this study it is known that 1) Parenting approach applied by parents is democratic parenting. Democratic approach is an approach that does not conflict with human values. 2. There are two ways to increase religious values, namely: (1) Contextual factual (2) Normative namely through traditional strategies, free strategies, reflective strategies, and transinternal strategies 3) Obstacles faced by parents are the children who are in disorders such as forgetful and stubborn, parents should be patient and gentle in guiding them.